The perceptions of academic staff of academic integrity policies and procedures and their responses to student plagiarism in Australian universities - De Maio, Carmela (Curtin University, 2015)
This study examines the perceptions of academic staff in Australian universities of institutional policies and procedures on academic integrity, and their understandings of, and responses to, ‘student plagiarism’. The findings suggest that academic staff have a clear understanding of plagiarism, find their institution’s policy fair but procedures difficult to follow. Reasons why responses to student plagiarism do not always align with the responses expected by institutions are outlined and a three view model is proposed.